2012
DOI: 10.1039/c2cp41179b
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal sterile alpha motif (SAM) domain of human p73 is a highly dynamic protein, which acquires high thermal stability through a decrease in backbone flexibility

Abstract: The α-splice variant of p73 (p73α), a homologue of the tumour suppressor p53, has close to its C terminus a sterile alpha motif (SAM), SAMp73, that is involved in protein-biomolecule interactions. The conformational stability of SAMp73 is low (∼5 kcal mol(-1)), although its thermal stability is high. To explain this high thermostability, we studied the dynamics of SAMp73 over a wide range of GdmCl (guanidine hydrochloride) concentrations and temperatures by NMR relaxation, NMR hydrogen-exchange (HX) and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…Finally, the values of S 2 from RSDA (eq ) qualitatively resembled those obtained by using the MF (Figure C), especially in the region around 40s, where there was a decrease in the S 2 values, as well as at the C terminus. Furthermore, there were some residues with a nonphysical value of S 2 larger than 1, which was probably due to their large J (0) values; similar findings have been observed in RSDA studies of highly mobile proteins. , …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, the values of S 2 from RSDA (eq ) qualitatively resembled those obtained by using the MF (Figure C), especially in the region around 40s, where there was a decrease in the S 2 values, as well as at the C terminus. Furthermore, there were some residues with a nonphysical value of S 2 larger than 1, which was probably due to their large J (0) values; similar findings have been observed in RSDA studies of highly mobile proteins. , …”
Section: Resultssupporting
confidence: 78%
“…Furthermore, there were some residues with a nonphysical value of S 2 larger than 1, which was probably due to their large J(0) values; similar findings have been observed in RSDA studies of highly mobile proteins. 60,61 ■ DISCUSSION Our present results showed that when PipX was isolated in solution, that is, it is not bound to its target proteins, its two αhelices were in close proximity. This conclusion is based on the interhelical NOEs found between the methyl groups of Leu65 and Leu80, located at α-helices 1 and 2, respectively (Figure 1B).…”
mentioning
confidence: 55%
“…Guanidinium chloride (gdmcl) is one of the most frequently used denaturants in studies of protein folding and unfolding and stability [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Gdmcl is also used in nucleic acid purification [15] and microfluidic nucleic acid probe assays [16].…”
Section: Introductionmentioning
confidence: 99%